Prevention and Management of Genital Mycotic Infections in the Setting of Sodium-Glucose Cotransporter 2 Inhibitors. Issue 4 (April 2021) - Engelhardt, Kristin; Ferguson, McKenzie; Rosselli, Jennifer L.
Objective: To review the incidence, risk factors, prevention, and management of genital mycotic infections (GMIs) associated with sodium-glucose cotransporter 2 (SGLT2) inhibitors. Data Sources: A literature search of PubMed and Reactions Weekly was performed in February 2020 with updated searches monthly through July 2020 to identify relevant data regarding SGLT2 inhibitors and GMIs. Manufacturers of each agent were contacted, and clinical practice guidelines were consulted. Study Selection and Data Extraction: All available literature was evaluated for inclusion based on relevance to the research question, timeliness of the publication, validity, and impact on current practice. A date limit was not set; however, publications from 2010 to July 2020 were prioritized. Data Synthesis: The 3- to 4-fold increased incidence of GMIs is considered a classwide effect of SGLT2 inhibitors. Female sex and a prior history of GMIs are factors associated with the highest risk, whereas circumcised males are at the lowest risk of SGLT2 inhibitor–induced GMI. Personal hygiene advice can reduce the infection risk. When candidiasis occurs, it is often mild and responsive to treatment and often does not require discontinuation of the medication. Relevance to Patient Care and Clinical Practice: This narrative review can assist in shared decision-making discussions with patients who may benefit from SGLT2 inhibitors and provides guidance for health care professionals managing SGLT2 inhibitor–associated GMIs. Conclusions: SGLT2 inhibitors predispose patients to developing mild GMIs. Strong consideration should be given to avoid SGLT2 inhibitors in female patients with a history of severe, recurrent infections. Preventive strategies are optimized diabetes management and personal hygiene advice.